The Economic Independence of Pesantren in Facing Economic Globalization : A Case Study of Pondok Pesantren Darul Falah Amtsilati, Jepara - Abdul Matin bin Salman; Muhammad Munadi; Tri Joko Susanto (Jurnal Ilmiah Ekonomi Islam, 2025)
This study examines the economic independence of pesantren (Islamic boarding schools) in responding to the challenges of economic globalization, using Pondok Pesantren Darul Falah Amtsilati Jepara as a case study. Employing a descriptive qualitative approach with field observations, interviews, and document analysis, the research explores how pesantren develop sustainable economic models grounded in Islamic values. The findings reveal that Darul Falah Amtsilati has successfully established a self-reliant economic ecosystem through diversified business units such as Amtsilati Water, Amtsilati Press, agriculture, livestock farming, and retail enterprises. These activities not only finance the pesantren’s operations but also foster entrepreneurship among students and the surrounding community. The study highlights the relevance of Dependency Theory in explaining pesantren’s historical reliance on external funding and shows how internal economic empowerment can reduce structural dependency. The pesantren’s economic independence model integrates education with entrepreneurship, aligns with Sharia economic principles, and strengthens community empowerment. Therefore, pesantren can serve as alternative Islamic economic institutions capable of promoting sustainable development and self-reliance within the context of global economic transformation. Keywords: Community empowerment, economic independence, globalization, Islamic economy, pesantren